Translation and identity: Translation of the Freedom Charter into Afrikaans as a case in point. Issue 3 (3rd July 2017) - Kassiem, Gava
Abstract: This article considers the relation between the activity of translation and identity formation with particular reference to the Afrikaner. To this end, various Afrikaans translations of the seminal political manifesto of South Africa, namely the Freedom Charter are considered. The Freedom Charter was a direct result of the inequalities upheld by the apartheid policy in South Africa and is therefore framed by a particular ideology – a sociopolitical ideology. While the main focus of the article is on identity formation, aspects linked to identity formation such as language, culture, ideology and patronage are also considered. Language has the power to alienate or include, as is the case with the Afrikaans language. The apartheid ideology resulted in Afrikaans carrying a political yoke since it was used as a means to construct a cultural and national identity of the Afrikaners. A comparative analysis of the Afrikaans translations reveals how the respective translators struggled sporadically through certain ideological constraints in order to provide a satisfactory narrative. Their inability to internalise the principles contained in the Freedom Charter resulted in them presenting a 'framed' translation product to their target audience. Translation scholar Mona Baker's narrative theory provides the premise for this article.